Peritoneal adhesions are an independent risk factor for peri- and post-partum infectious morbidity. (October 2019) - Saban, Alla; Shoham-Vardi, Ilana; Yohay, David; Weintraub, Adi Y.
Abstract: Objective: To investigate whether the presence of peritoneal adhesions during a second cesarean delivery resulting from the first cesarean delivery, are associated with peri- and post-partum infectious morbidity. Study Design: A retrospective cohort study was undertaken, comparing maternal peri- and immediate post-partum infectious morbidity during the second cesarean delivery, between women with and without adhesions resulting from the first cesarean delivery. All women over 18 years old at their second cesarean delivery, with a singleton pregnancy between the years 1988–2016 were included in the analysis. Patients with previously diagnosed adhesions during the first cesarean delivery, a history of other abdominal or pelvic surgery, pelvic infection or pelvic inflammatory disease, endometriosis, uterine Mullerian anomalies, and births of newborns with known chromosomal or structural abnormalities were excluded from the analysis, resulting in a study population of 7925 women. Infectious morbidity was defined as a composite of chorioamnionitis, post-partum fever, urinary tract infection and surgical wound infection or disruption. In order to identify factors that are independently associated with infectious morbidity, multivariate logistic regression analyses were constructed to control for potential confounders. Results: During the study period, 32.6% (n = 2581) women were diagnosed with adhesions at the second cesarean delivery. Second cesarean deliveries complicated with adhesions were characterized by higher rates of peri- and post-partum maternal infectious morbidity (6.5% vs. 9%, p < 0.001). Our study population comprises two ethnic groups- Jewish (54.3%) and Bedouin Arabs (45.7%). We have tested interactions with adhesions of all predictor variables in the model. Since we found a strong interaction between adhesions and ethnicity, stratified data are presented. Infectious morbidity was significantly associated with the presence of peritoneal adhesions only among Jewish women (adjusted OR 2.09, PV < 0.001, 95% CI 1.56–2.80), adjusting for potential confounding variables and significant interactions. Conclusion: Cesarean delivery complicated with adhesions attributable to a previous cesarean delivery, increase the risk for peri- and immediate post-partum infectious morbidity among Jewish women.